Adapting Mindfulness Training for Military Service Members With Chronic Pain. Issue 3 (17th October 2019) - Brintz, Carrie E; Miller, Shari; Olmsted, Kristine Rae; Bartoszek, Michael; Cartwright, Joel; Kizakevich, Paul N; Butler, Michael; Asefnia, Nakisa; Buben, Alex; Gaylord, Susan A
Abstract: Introduction: Rates of chronic pain in military personnel are disproportionately high. Chronic pain is often associated with mental health and substance use disorders as comorbid conditions, making treatment of chronic pain complex. Mindfulness-based interventions (MBIs) are a promising behavioral approach to managing chronic pain and psychosocial sequelae. The unique nature of the military context may require adaptations to original MBIs for successful delivery in active-duty military populations. This study adapted the mindfulness-based stress reduction (MBSR) program to create a mindfulness training program that was relevant to active-duty Army personnel experiencing chronic pain. This article delineates the adaptation process employed to modify the MBSR program to the military context and discusses the resulting training program. Materials and Methods: The adaptation process consisted of three iterative stages: 1) Drafting the preliminary intervention protocol with recommendations from stakeholders, including military healthcare providers; 2) Refining the preliminary protocol after pretesting the sessions with research team members and a military Veteran advisory committee; and 3) Delivering the preliminary protocol to one cohort of active-duty Soldiers with chronic pain, collecting feedback, and further refining the intervention protocol. Results: Military-related adaptations to MBSR addressed three areas: military culture, language and terminology, and practical and logistical factors relevant to implementation in the military setting. This adaptation process resulted in a live, online program with six, weekly, sessions. Feedback from a military Veteran advisory committee resulted in modifications, including increasing military-relevant examples; preliminary testing with the target population resulted in additional modifications, including shortening the sessions to 75 min and structuring discussions more efficiently. Conclusions: The adaptation process was successful in generating an engaging mindfulness training program that was highly relevant to the military context. Obtaining input from stakeholders, such as military healthcare providers and active-duty soldiers, and iterative feedback and modification, were key to the process. Moreover, the program was designed to maintain the integrity and core elements of MBIs while adapting to military culture. A future randomized controlled trial design will be used to evaluate the effectiveness of the intervention in improving chronic pain in military personnel. This program is responsive to the military's call for nonpharmacologic treatments for chronic pain that are easily accessible. If effective, the mindfulness program has the potential for widespread dissemination to complement standard care for Service Members experiencing chronic pain.